2020
DOI: 10.15252/embr.201949799
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA in inflammation and immunity

Abstract: Mitochondria are cellular organelles that orchestrate a vast range of biological processes, from energy production and metabolism to cell death and inflammation. Despite this seemingly symbiotic relationship, mitochondria harbour within them a potent agonist of innate immunity: their own genome. Release of mitochondrial DNA into the cytoplasm and out into the extracellular milieu activates a plethora of different pattern recognition receptors and innate immune responses, including cGAS‐STING, TLR9 and inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
385
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 529 publications
(473 citation statements)
references
References 214 publications
(271 reference statements)
8
385
1
3
Order By: Relevance
“…4,6 In the normal physiological setting, mtDNA within cells is being constantly replicated and replaced via degradation during the mitochondrial life cycle and can act as a signalling molecule. 10 However, if the mitochondrial life cycle is disrupted and the degradation of damaged mtDNA is impaired, mtDNA can leak out of the mitochondria into the cytosol or the peripheral circulation. Due to its resemblance to bacterial genomes, this cell-free (cf) mtDNA can activate the TLR-9 pathway, leading to activation of TNF-alpha and a downstream inflammatory response.…”
mentioning
confidence: 99%
“…4,6 In the normal physiological setting, mtDNA within cells is being constantly replicated and replaced via degradation during the mitochondrial life cycle and can act as a signalling molecule. 10 However, if the mitochondrial life cycle is disrupted and the degradation of damaged mtDNA is impaired, mtDNA can leak out of the mitochondria into the cytosol or the peripheral circulation. Due to its resemblance to bacterial genomes, this cell-free (cf) mtDNA can activate the TLR-9 pathway, leading to activation of TNF-alpha and a downstream inflammatory response.…”
mentioning
confidence: 99%
“…Perhaps the differences (or lack thereof) in mitochondrial-gene expression are a byproduct of mitochondrial small open reading frame post-transcriptional regulation or the immune-signaling capacity of mitochondrial RNA and DNA released into the cytoplasm. [14][15][16] Second, we found that SARS-CoV-2 did not alter MAVS expression, whereas IAV, HPIV, and RSV all decreased MAVS expression. Although SARS-CoV-2 differentially regulates the host cell's interferon response, MAVS is not directly regulated by interferons.…”
Section: Discussionmentioning
confidence: 64%
“…For instance, the most prominent hit with pan-viral antiviral activity was IRF1, a transcription factor responsible for IFN-independent induction of some ISGs. The same screen also identified the DNA-sensor cGAS as a gene with broad antiviral function against DNA-, but also RNA viruses, which may partially be explained by virus-mediated secondary effects such as mitochondrial damage [ 58 , 59 ].…”
Section: Genetic Screensmentioning
confidence: 99%